THE EFFECT OF HEALTH EDUCATION ABOUT MENARCHE ON ANXIETY IN FACING MENARCHE IN 5TH AND 6TH GRADE STUDENTS - Surya Mustika Sari; Henny Vidia Effendy (Nurse and Health: Jurnal Keperawatan, 2019)
Background: Important events during puberty are menstruation or menarche is a sign of sexual maturity. The causes of young men and women are not aware of their health problems, especially regarding menarche, this causes young women to have an understanding of menarche and lead to anxiety in the face of menarche in adolescent’s daughter.Objectives: This study aimed to determine the effect of health education about menarche on anxiety in facing menarche in 5th and 6th grade students at SDIT Permata Mulia.Methods: This study design using pre-experimental design with one group pre-post-test design. Sampling method using Non-Probability Sampling with saturated sampling type. Samples taken as many as 28 res ponders on V and VI graders at SDIT Permata Mulia. The research data using a questionnaire. The data were analysed using the Wilcoxon test with a significance level of 0.05.Results: Anxiety student before being given health education about menarche mostly moderate anxiety at (53.6%). While anxiety after students are given health education about menarche, mostly mild anxiety (57.1%). Statistical test results obtained ρ = 0.00 <α = 0.05 then H0 is rejected and H1 is accepted, which means that there is a difference between health education about grade V and VI in SDIT Permata Mulia.Conclusion: Seeing the results of this study about health education about menarche can help in reducing female anxiety in the face of menarche, the role of parents and educators is needed in providing an explanation of menarche to children in grades V and VI aged 11-12 years including maintaining personal hygiene in genital, provide knowledge to students that menarche will occur in all women. Keywords: Health education, Menarche, Anxiety